Impact of Prolonged Cardiopulmonary Bypass and Aortic Cross-Clamp Time on Postoperative Ventilator Dependency Following Mitral Valve Replacement - Aswin Nugraha; Reizkhi Fitriyana; Erial Bahar (Sriwijaya Journal of Surgery, 2025)
Introduction: Mitral valve replacement (MVR) is a common procedure for severe mitral valve disease. Prolonged cardiopulmonary bypass (CPB) time and aortic cross-clamp (AOX) time during cardiac surgery are known to be associated with adverse postoperative outcomes, including prolonged mechanical ventilation. Understanding the predictive value of these intraoperative times specifically for ventilator dependency after MVR is crucial for risk stratification and patient management. This study aimed to determine the accuracy of CPB time and AOX time as predictors of postoperative ventilator duration in patients undergoing MVR at a tertiary referral hospital in Palembang, Indonesia. Methods: A retrospective cohort study was conducted using medical records of patients aged ≥ 18 years who underwent MVR between January 2022 and December 2024 at RSUP Dr. Mohammad Hoesin Palembang. Data from 79 patients meeting the inclusion criteria were analyzed. The primary independent variables were CPB time and AOX time (categorized using a 90-minute cut-off). The primary outcome was prolonged mechanical ventilation (defined as >24 hours). Secondary outcomes included ICU length of stay (>4 days) and in-hospital mortality. Statistical analysis involved Chi-square tests and multivariate logistic regression. Results: Prolonged CPB time (≥90 minutes) was observed in 62% of patients, and prolonged AOX time (≥90 minutes) in 45.6%. Both prolonged AOX time (OR 15.167, p=0.01) and prolonged CPB time (OR 8.88, p=0.01) were significantly associated with mechanical ventilation >24 hours. Multivariate analysis confirmed both AOX time (Adjusted OR 8.741, p=0.049) and CPB time (Adjusted OR 5.163, p=0.027) as independent predictors for prolonged ventilation. Significant associations were also found between prolonged AOX/CPB times and ICU stay >4 days (p=0.03 for both). No significant association was found between CPB/AOX times and in-hospital mortality (p=0.968 and p=0.206, respectively). Conclusion: Prolonged CPB time and AOX time are significant independent predictors of postoperative ventilator dependency exceeding 24 hours following MVR in this patient cohort. Minimizing these intraoperative durations may reduce the burden of prolonged mechanical ventilation.